A Comparison of Lipid Profile Between Sedentary and Non Sedentary Workers (TAJ: Journal of Teachers Association, 2010)
In different epidemiological studies, an association between sedentary life style and incidence of cardiovascular diseases has been demonstrated. Dyslipidaemia is one of the important risk factors of cardiovascular disease. An association of dyslipidaemia with sedentary life style has been considered. This study was carried out among 50 sedentary workers (teachers, office staffs, bank employees) at Pabna District and 50 individuals with non-sedentary jobs matched for age group and sex for the control group to see the association. Body mass index (BMI), blood pressure (BP), plasma level of glucose, total cholesterol, low density lipoprotein (LDL), and triglycerides (Tgs) were found to be significantly higher whereas high density lipoprotein (HDL) was found to be significantly lower among the sedentary workers as compared with the control subjects. From the study, it appears that dyslipidaemia is more common in sedentary workers and the relative risk for cardiovascular disease is increased among them due to the sedentary nature of their jobs. DOI: 10.3329/taj.v22i1.5014 TAJ 2009; 22(1): 10-14